Mean platelet volume/platelet count ratio in hepatocellular carcinoma. (August 2013) - Cho, Sun Young; Yang, John Jeongseok; You, Eunkyoung; Kim, Byung-Ho; Shim, Jaejun; Lee, Hee Joo; Lee, Woo-In; Suh, Jin-Tae; Park, Tae Sung
<x xml:space="preserve">Abstract</x> Mean platelet volume (MPV) has been actively investigated in liver disease such as steatosis, cirrhosis and hepatitis. Recently, MPV/platelet count (PC) ratio has been proposed as a predictor of long-term mortality after myocardial infarction. As PC is known to be decreased in various liver diseases such as cirrhosis, hepatosplenomegaly and malignancy, we planned to evaluate MPV/PC ratio in patients with hepatocellular carcinoma (HCC) in this study. Mean of MPV levels showed significant difference, which were 8.69 fl (range 6.7–12.2 fl) in patients group and 8.02 fl in control group (range 6.7–11.0 fl). In receiver operating characteristic (ROC) curve analysis, the MPV/PC ratio (fl/(109/l)) presented 74.5% of sensitivity and 96.5% of specificity at the criterion > 0.0491 (area under the curve (AUC) = 0.884), while MPV alone showed 57.4% of sensitivity and 81.4% of specificity at the criterion > 8.4 fl. Further studies should evaluate underlying pathogenic mechanisms of MPV/PC ratio difference and various possibilities of this ratio as an indicator of presence of a tumor in HCC.